(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Landslides are very often in mountain areas like Himalya region. Landslide causes loss to man, his properties and ongoing development projects. Landslides are majorly found after heavy rains when a lot of water penetrates into the soil resulting in inner pressure and landslide takes place. Deforestation is considered as the big reason for the landslide as in empty soil, most of the rain water penetrates into the soil and pressure forces for landslide. However, some geologists considered the type of rock, nature of rock and other parameters like angle, tetonic deformation etc. for the phenomenon of landslide and the inner structure of rock is analyzed. The current article highlights the mapping of geomatics based optimum landslide using remote sensing GIS approach.